2015
DOI: 10.2105/ajph.2015.302855
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Bullying and Suicidal Ideation: A 3-Wave Longitudinal Norwegian Study

Abstract: Workplace bullying may be a precursor to suicidal ideation, whereas suicidal ideation seems to have no impact on subsequent risk of being bullied. Regulations against bullying should be integrated into work-related legislation and public health policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
82
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 34 publications
4
82
0
3
Order By: Relevance
“…This study, which extends previously published data (6,13), was based on a three-wave survey of a representative sample of Norwegian employees (14,15). Time-lags between surveys were two (T1-T2) and five years (T1-T3).…”
Section: Methodssupporting
confidence: 62%
See 2 more Smart Citations
“…This study, which extends previously published data (6,13), was based on a three-wave survey of a representative sample of Norwegian employees (14,15). Time-lags between surveys were two (T1-T2) and five years (T1-T3).…”
Section: Methodssupporting
confidence: 62%
“…This makes a strong case for arguing that exposure to bullying constitutes a risk factor for suicidal ideation (6). While there is theoretical and empirical evidence for bullying as a risk factor for suicidal ideation, previous studies have not provided information about the particular behavioral content of the bullying.…”
Section: Nielsen Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…1 Professor Emeritis, Southern Illinois University he or she becomes physically ill, resigns, or, in extreme cases, commits suicide (Nielsen, Nielsen, Notelaers, & Einarsen, 2015). Neuroscientists distinguish between (a) general intelligence, which consists of reasoning and memory, and (b) social intelligence, or empathic capacity, which gives us compassion and a conscience.…”
Section: Social Intelligencementioning
confidence: 99%
“…Psychological and psychosomatic reactions become more prominent and severe with persistent exposure. Illustrating these reactions, research shows that prolonged bullying is associated with subsequent reports of anxiety (8,15), depression (8,16), suicidal ideation (17,18), headache (19), and sleep problems (20)(21)(22). In a meta-analysis it was found that exposure to bullying predicted subsequent mental health complaints [odds ratio (OR) 1.68, 95% confidence interval (95% CI) 1.35-2.09] and somatic complaints (OR 1.77, 95% CI 1.41-2.22) after adjusting for baseline health status (9).…”
mentioning
confidence: 99%